2013
DOI: 10.1007/s11999-013-3086-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Proximal Rectus Femoris Release Influence Kinematics In Patients With Cerebral Palsy and Stiff Knee Gait?

Abstract: Background Stiff gait resulting from rectus femoris dysfunction in cerebral palsy commonly is treated by distal rectus femoris transfer (DRFT), but varying outcomes have been reported. Proximal rectus femoris release was found to be less effective compared with DRFT. No study to our knowledge has investigated the effects of the combination of both procedures on gait. Questions/purposes We sought to determine whether an additional proximal rectus release affects knee and pelvic kinematics when done in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Donald Neumann summarized the kinesiology of the hip and indicated that “a sufficiently strong and isolated bilateral contraction of any hip flexor muscle will either rotate the femur towards the pelvis, the pelvis (and possibly the trunk) towards the femur, or both actions simultaneously” [20]. The proximal part of the rectus femoris plays an important role in pelvic tilt and hip flexion [21]. As the knee joints were locked in both KAI and KI gait, and the hip angles did not present significant differences in the single support phase, therefore, the increased RF and RA activation could provide the power for more anterior pelvic tilt in KAI gait.…”
Section: Discussionmentioning
confidence: 99%
“…Donald Neumann summarized the kinesiology of the hip and indicated that “a sufficiently strong and isolated bilateral contraction of any hip flexor muscle will either rotate the femur towards the pelvis, the pelvis (and possibly the trunk) towards the femur, or both actions simultaneously” [20]. The proximal part of the rectus femoris plays an important role in pelvic tilt and hip flexion [21]. As the knee joints were locked in both KAI and KI gait, and the hip angles did not present significant differences in the single support phase, therefore, the increased RF and RA activation could provide the power for more anterior pelvic tilt in KAI gait.…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical approaches to stiff knee gait have been used over time, such as proximal or distal rectus femoris release and distal rectus femoris transfer (DRFT). 2 - 17 Computerized movement analysis data are often useful in the assessment of patients with stiff knee gait but there remains considerable variability in interpretation of underlying mechanisms and surgical decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized gait analysis has been used for identifying more detailed changes in walking performance in CP patients before and after tenotomy [ 13 17 ]. Depending on the location of the surgery, tenotomy was found to help one or more of the following: decreased hip flexion contracture, increased knee extension during stance, decreased knee flexion during swing and decreased ankle plantarflexion throughout the gait cycle [ 13 16 ]. Since the different joints and muscles of the lower extremities work together to meet the varying mechanical and balance demands during different phases of gait, changing the tightness of one muscle may affect the actions of the other muscles, and thus the motions of the joints.…”
Section: Introductionmentioning
confidence: 99%